Book profile: Holiness, speech and silence - Bell, Daniel M. (The journal for cultural and religious theory, 2005)
A profile of Nicholas Lash’s Holiness, Speech and Silence: Reflections on the Question of God. Ashgate Publishing, 2004. 98 pp. $24.95 (paper). ISBN 0-7546-5039-1.